2009
DOI: 10.1104/pp.109.145722
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sodium and Potassium Transport Selectivities of the Rice OsHKT2;1 and OsHKT2;2 Transporters in Plant Cells    

Abstract: Na(+) and K(+) homeostasis are crucial for plant growth and development. Two HKT transporter/channel classes have been characterized that mediate either Na(+) transport or Na(+) and K(+) transport when expressed in Xenopus laevis oocytes and yeast. However, the Na(+)/K(+) selectivities of the K(+)-permeable HKT transporters have not yet been studied in plant cells. One study expressing 5' untranslated region-modified HKT constructs in yeast has questioned the relevance of cation selectivities found in heterolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 86 publications
3
132
0
1
Order By: Relevance
“…Ca 2+ was demonstrated to inhibit Na + transport through NSCCs and LCT1 Tester 2000, Amtmann et al 2001). Recent research showed that Ca 2+ inhibited OsHKT2; 1-mediated Na + influx into plant cells (Yao et al 2010). Therefore, Ca 2+ plays important role in regulating apoplast and symplast pathways involved in Na + transport.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ was demonstrated to inhibit Na + transport through NSCCs and LCT1 Tester 2000, Amtmann et al 2001). Recent research showed that Ca 2+ inhibited OsHKT2; 1-mediated Na + influx into plant cells (Yao et al 2010). Therefore, Ca 2+ plays important role in regulating apoplast and symplast pathways involved in Na + transport.…”
Section: Discussionmentioning
confidence: 99%
“…These results have led to hypothesize that HKT2;1 subgroup transporters only work as Na + uniporters in planta (Haro et al, 2005;Horie et al, 2007), and that the Na + -K + symport mode evidenced in yeast or Xenopus oocytes is artifactual, resulting from the heterologous context, or anecdotal in planta. It should however be noted that the rice OsHKT2;2 transporter has recently been shown to have the capacity to mediate K + transport in a plant context, when overexpressed in cultured tobacco (Nicotiana tabacum) cells (Yao et al, 2010). Since OsHKT2;4 appears highly K + permeable in all its conducting modes and can even mediate pure K + transport at low external Na + concentrations when expressed in Xenopus oocytes (Figs.…”
Section: Oshkt2;4 Is Selective For K + Among Monovalent Cationsmentioning
confidence: 99%
“…There is no doubt that Na + , when appearing suddenly at high concentrations, in "shock" scenarios (see discussion in Cheeseman 2013), carries osmotic consequences that disrupt, typically temporarily, the membrane integrity of roots (Britto et al 2010;Coskun et al 2013), or also those of shoots, such as shown in rice (Flowers et al 1991), preceding, or perhaps coinciding with, more "ion-specific" effects (see later discussions). In addition to this well-recognized osmotic effect, a second parsimonious explanation may lie in the disruption of potassium homeostasis-one that may reasonably and fruitfully supplant alternative, to date ill-substantiated , hypotheses, such as those of "toxic" Na + fluxes or cytosolic K + /Na + ratios (Maathuis and Amtmann 1999;Davenport and Tester 2000;Yao et al 2010; see below). The decline in cytosolic [K + ] ([K + ] cyt ) under saline conditions is well documented (Hajibagheri et al 1987(Hajibagheri et al , 1988Binzel et al 1988;Schroeppel-Meier and Kaiser 1988;Speer and Kaiser 1991;Hajibagheri and Flowers 2001;Carden et al 2003;Kronzucker et al 2006; see also Fig.…”
Section: Sodium Toxicitymentioning
confidence: 99%